Covid-19: The Newest Black Swan Crisis and Its Effect toward Banking Stocks - Nibras Anny Khabibah; Faqiatul Mariya Waharini (Jurnal Riset Akuntansi dan Keuangan, 2022)
Abstract. The outbreak of Covid-19 has changed the condition of stock markets around the world, including Indonesia. The bad news regarding this latest pandemic is forming negative sentiment in the market. Banking companies are one of the industries that have been shaken by the virus. The decline in performance and losses that occurred in many companies due to Covid-19 increased the risk of bad bank loans. This study aims to identify the effect of Covid-19 on the reaction of the banking market in Indonesia. Here, the market reaction is measured by changes in stock prices and stock trading volumes before and after the presidential announcement regarding the Covid-19 case. This study uses the efficient market hypothesis and signal theory to explain the reaction. Data analysis was tested using the Wilcoxon Signed Rank Test. The results showed that there was a change in the price of banking shares and trading volume of banking shares after the entry of Covid-19 in Indonesia.